1986
DOI: 10.1177/002221948601900406
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of The Minnesota Perceptual Diagnostic Test Revised And The Bender Gestalt

Abstract: determine if either perceptual motor test provides unique information abut the cognitive-perceptual abilities of children. Thirty-three children were given the WISC-R, WRAT, Bender Gestalt and MPDT-R. Multiple regression analyses with the Bender and the MPDT-R as predictor variables were used to predict intellectual and academic performance. These analyses indicated that the MPDT-R was clearly superior to the Bender in prediction of WISC-R Full 1Qand WRAT spelling and math scores. Neither perceptual motor test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…Diversos pesquisadores nacionais e estrangeiros têm utilizado o Teste Gestáltico Viso-Motor de Bender em seus estudos (Arrillaga, Eschebarria & Goya, 1981;Bandeira & Hutz, 1994;McCarron & Horn, 1979;Vance, Fuller & Lester, 1986; entre outros). Grande parte dessas pesquisas foi realizada com base no sistema de avaliação de Koppitz, no entanto, há algum tempo, muitos estudos têm detectado problemas em sua discriminação da habilidade viso-motora e ressaltado seu poder restrito de aplicação fora do local onde foi desenvolvido (Bartholomeu, 2004;Bartholomeu, Rueda & Sisto, 2005;Britto & Santos, 1996;Chan, 2001;Kroeff, 1992;Neale & McKay, 1985;Pinelli Jr. & Pasquali, 1991/1992Silvestre, Salaverry & Gonzales, 1995;.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Diversos pesquisadores nacionais e estrangeiros têm utilizado o Teste Gestáltico Viso-Motor de Bender em seus estudos (Arrillaga, Eschebarria & Goya, 1981;Bandeira & Hutz, 1994;McCarron & Horn, 1979;Vance, Fuller & Lester, 1986; entre outros). Grande parte dessas pesquisas foi realizada com base no sistema de avaliação de Koppitz, no entanto, há algum tempo, muitos estudos têm detectado problemas em sua discriminação da habilidade viso-motora e ressaltado seu poder restrito de aplicação fora do local onde foi desenvolvido (Bartholomeu, 2004;Bartholomeu, Rueda & Sisto, 2005;Britto & Santos, 1996;Chan, 2001;Kroeff, 1992;Neale & McKay, 1985;Pinelli Jr. & Pasquali, 1991/1992Silvestre, Salaverry & Gonzales, 1995;.…”
Section: Discussionunclassified
“…Ao lado disso, tem sido empregado como teste de inteligência e como medida de personalidade em adolescentes, bem como na predição do desempenho escolar e determinação da necessidade de psicoterapia (Arrillaga, Eschebarria & Goya, 1981;Bandeira & Hutz, 1994;Bartholomeu, Rueda & Sisto, 2005;Byrd, 1956;Koppitz, 1989;McCarron & Horn, 1979;Pinelli Jr. & Pasquali, 1991/ 1992Sisto, Bueno & Rueda, 2003;Vance, Fuller & Lester, 1986).…”
unclassified
“…Previous studies (Fuller & Vance, 1993;Fuller & Wallbrown, 1983; Vance et al, 1986) have indicated that the MPD was more sensitive than the Bender in identifying areas of achievement for young children as well as older children. Fuller and Vance (1993) investigated whether the MPD-R or the Bender would more accurately predict achievement at the first-, third-, and fifth-grade levels.…”
mentioning
confidence: 94%
“…It offers an objective scoring system for individuals 5 years of age to adult. To date, the test has been shown to differentiate between braindamaged and non-brain-damaged subjects (Fuller & Levine, Vance et al, 1986) have indicated that the MPD was more sensitive than the Bender in identifying areas of achievement for young children as well as older children. Fuller and Vance (1993) investigated whether the MPD-R or the Bender would more accurately predict achievement at the first-, third-, and fifth-grade levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation